1996
DOI: 10.1038/ki.1996.300
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the thiazide sensitive Na-Cl cotransporter, rTSC1, in the rat kidney

Abstract: A thiazide sensitive Na-Cl cotransporter, rTSC1, has recently been cloned from a rat kidney cortex cDNA library. The molecular regulation and nephron localization of this protein is unknown. The purpose of this study was to examine the nephron distribution and subcellular localization of the rTSC1 protein in the rat kidney. In situ hybridization showed rTSC1 transcripts were localized to short, convoluted tubule segments in the kidney cortex. Polyclonal antibodies raised against a 110 amino acid segment from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
128
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(139 citation statements)
references
References 7 publications
9
128
0
2
Order By: Relevance
“…Immunocytochemical analysis revealed that hNCC was present in the apical domain of the cell, with virtually no staining at the basolateral side. This is in agreement with the observation that in rat, NCC is localized predominantly on apical microvilli of cells lining the DCT (12). The observed increase in thiazide-inhibitable Na ϩ uptake and transepithelial transport indicates that at least part of the cotransporter is functional and therefore present in the apical membrane.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Immunocytochemical analysis revealed that hNCC was present in the apical domain of the cell, with virtually no staining at the basolateral side. This is in agreement with the observation that in rat, NCC is localized predominantly on apical microvilli of cells lining the DCT (12). The observed increase in thiazide-inhibitable Na ϩ uptake and transepithelial transport indicates that at least part of the cotransporter is functional and therefore present in the apical membrane.…”
Section: Discussionsupporting
confidence: 79%
“…This versatility in function reveals itself differences in patterns of tissue expression and cellular localization (11). NCC is present on the apical membranes of DCT (12), whereas NKCC2 is apically expressed in the thick ascending limb of the loop of Henle (13). Whole-animal studies have implicated the mineralocorticoid hormone aldosterone and the sex hormone estradiol in the regulation of NCC expression.…”
mentioning
confidence: 99%
“…7 The two-dimensional structure of NCC is predicted to contain 12 transmembrane segments (S) with large intracellular amino (N)-and carboxy (C)-terminal regions, and a large hydrophilic extracellular loop between S7 and S8. 8 NCC localizes to the luminal membrane of the DCT segment of the nephron, 9 where it facilitates the cotransport of Na + and Cl À from the pro-urine to the intracellular compartment.…”
Section: Introductionmentioning
confidence: 99%
“…This cotransporter mediates the apical reabsorption of Na ϩ with Cl Ϫ and is expressed predominantly in the distal convoluted tubule (9,10). Consequently, the expression of WNK4 and NCCT overlap in epithelial cells of the distal nephron.…”
mentioning
confidence: 99%